Stepping Up to Edge Hill University: the value and impact for students following the completion of a virtual pre-entry module - Helen Jamieson (Association for Learning Development in Higher Education (ALDinHE), 2019)
As learning developers, our main role is to support students in developing their academic skills throughout their time at university. We are particularly interested in students’ transition into university and have developed a programme-specific pre-entry module within Blackboard Open Education to support undergraduate students with their transition into their academic programme of study. As part of a pedagogical research project for the Postgraduate Certificate in Teaching in Higher Education (PGCTHE), we have attempted to assess the value and impact of this pre-entry module. Our project employed a mixed methods analysis of a wide range of quantitative and qualitative data, including student conversion data (Quercus Student Records System); module engagement and completion data (Blackboard Open Education); student satisfaction data (Bristol Online Survey); value and impact data from key academic staff (semi-structured interviews) and students (focus group/semi-structured interview and Bristol Online Survey); and a thorough review of associated literature. We shared our preliminary findings at the Association for Learning Developers in Higher Education conference (ALDHE) in Exeter in April 2019. Our research has shown that, although student satisfaction is high with some indication of added value and a positive impact on the students’ transitional experience, these are self-reported and we thus conclude that this research would benefit from further exploration and more extensive student, stakeholder and platform evaluation.